Radiation effects on submandibular gland of the rat. Stereological and ultrastructural study - Espinal, E. G.; Molinari de Rey, Beatriz L.; Cabrini, Rómulo Luis (1983)
Fil: Espinal, E. G. Comisión Nacional de Energía Atómica; Argentina